2018
DOI: 10.1371/journal.pone.0206427
|View full text |Cite
|
Sign up to set email alerts
|

The autophagy inhibitor spautin-1, either alone or combined with doxorubicin, decreases cell survival and colony formation in canine appendicular osteosarcoma cells

Abstract: Dogs diagnosed with appendicular osteosarcoma typically succumb to metastatic disease within a year of diagnosis. The current standard of care for curative intent, amputation followed by adjuvant chemotherapy, increases survival time but chemoresistance is a major contributor to mortality. Unfortunately, the mechanisms driving the progression of metastatic disease and the development of chemoresistance are unknown. One theory is that autophagy may contribute to chemoresistance by providing neoplastic cells wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 72 publications
1
24
0
Order By: Relevance
“…In this study, effort was invested on optimizing a specific assay through use of multiple antibodies to exclude nonspecific antibody binding to extracellular or intracellular epitopes of OSA cells, distinction of leukocytes from OSA cells, and assuring that only viable single cells were being assessed. Initial optimization experiments utilizing cell lines derived from a primary and a metastatic tumor showed slightly differing light scatter properties, consistent also with differing biological properties and signaling pathways of these cell lines (33). Both cell lines had moderate to high FSC but OVC-cOSA-75 cells had low SSC.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In this study, effort was invested on optimizing a specific assay through use of multiple antibodies to exclude nonspecific antibody binding to extracellular or intracellular epitopes of OSA cells, distinction of leukocytes from OSA cells, and assuring that only viable single cells were being assessed. Initial optimization experiments utilizing cell lines derived from a primary and a metastatic tumor showed slightly differing light scatter properties, consistent also with differing biological properties and signaling pathways of these cell lines (33). Both cell lines had moderate to high FSC but OVC-cOSA-75 cells had low SSC.…”
Section: Discussionmentioning
confidence: 75%
“…Cell lines OVC-cOSA-75 and OVC-cOSA-31 were derived from autopsy and amputation specimens from two separate dogs with lung metastases or primary OSA of the distal tibia, respectively (33). Cell lines were established and maintained as monolayers in DMEM (Sigma Aldrich, Oakville, ON) supplemented with 10% fetal bovine serum (Fisher Scientific, Ottawa, ON) and 1% penicillin/streptomycin (Sigma Aldrich), and cultured at 37 C in a humidified incubator in the presence of 95% atmospheric air and 5% CO 2 .…”
Section: Immortalized Osa Cell Linesmentioning
confidence: 99%
“…The chemotherapeutic agent Dox induces autophagy in human osteosarcoma cell lines [23]. Autophagy contributes to chemoresistance in canine appendicular osteosarcoma and adding an autophagy inhibitor to the standard of care has the potential to improve outcome [15]. In the present study, we constructed a Dox-resistant U2OS cell subtype, U2OS/Dox, and consistently observed that autophagy inhibitor 3-MA could resensitize U2OS/Dox to Dox treatment.…”
Section: Agingmentioning
confidence: 56%
“…Autophagy might be one mechanism by which neoplastic cells maintain survival upon chemotherapy treatment. Under such conditions, blocking autophagy could trigger apoptosis, therefore enhancing the curative effects of these chemotherapies and reducing chemoresistance [15,16]. Here, we constructed a Doxresistant U2OS cell line, U2OS/Dox, by treating…”
Section: Dox Treatment Induces Autophagy and Sox2ot-v7 Expression In mentioning
confidence: 99%
“…Considering the role of autophagy in OS treatment resistance, many studies combined the use of anti-cancer agents with autophagy inhibitors such as chloroquine, 3-methyladenine or spautin-1 (specific and potent autophagy inhibitor-1). These autophagy inhibitors enhance OS cell death induced by cisplatin [73], doxorubicin [74], bone-targeted gallium compound KP46 [75], and increase in vivo tumor regression following photodynamic therapy [76] or mTOR inhibition [77].…”
Section: Autophagy In Osteosarcomamentioning
confidence: 99%